Protocol to study the role of medial entorhinal cortex-basolateral amygdala circuit in context-induced retrieval of morphine withdrawal memory in mice - Yali Fu; Ting Ye; Ming Chen; Bin Lai; Ping Zheng (STAR Protocols)
Summary: The medial entorhinal cortex (MEC) is crucial for context memory, yet its role in context-induced retrieval of morphine withdrawal memory remains to be investigated. Here, we present a protocol to evaluate the importance of projection neurons from the MEC to the basolateral amygdala (BLA) (MEC-BLA neurons) in mice during context-induced retrieval of morphine withdrawal memory using a conditioned place aversion (CPA) model. We describe steps for surgical procedure and behavioral experiments. Then, we detail procedures of immunofluorescence staining and image analysis.For complete details on the use and execution of this protocol, please refer to Fu et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.